(untitled) (Journal of the College of Basic Education, 2023)
Talk shows are one of the types widely used in most of the terrestrial and satellite television channels, due to its ease of production compared to other types of television programs, which made it the most used, especially in urgent or immediate topics, whether local, regional or global events, in addition to its use in various political - economic - topics. Social-sports-artistic and other topics. Therefore, this type of program occupies a special importance in the map of television programs, especially if the appropriate topic, guests and axes are chosen well.